Incidence and Management of Gynecological Complaints Presented as Acute Abdomen in the General Surgery Emergency Department - Dr. Ali Abdul-Hussein Kareem; Dr. Burair Zuhair Jaafar; Dr. Mohammed Hikmat Farman (Academic Journal of Clinicians, 2024)
Objectives: To evaluate the emergencies in gynecological complaints seen as an acute abdomen in general surgery emergency department in term of incidence and management. Methods: A prospective descriptive study was done at Al-Emamain Alkadhemain Medical City for a period from October,1st 2017 to October,1st 2018. The study enrolled 340 female patients presented to the surgical emergency department with non-traumatic acute abdomen, 44 patients were turned to have underlying gynecological pathologies by surgical interventions after full assessment by clinical history, examination, investigations and resuscitation. Results: Among 340 female patients, a total of 44(12.9%) patients were found to have gynecological pathology as a cause of acute (72.7%) were presented as right iliac fossa pain and tenderness. Ultrasound of abdomen was done for all patients but were not conclusive in most of the cases (67%). The majority of patients were explored through a grid Iron incision (73.9%). The most common gynecological problem was found to be due to ruptured ovarian cyst (60.2%) and the least common was abdomenal endometriosis (1.1%). Conclusion: Gyne-obstetrical emergencies represent an appreciable percent in general surgical practice especially in Grid-Iron incision for acute abdomen, therefore, acute abdominal symptoms in females need a thorough work up due to variable presentations, diagnoses and management options.